2016
DOI: 10.1021/acs.jpcc.6b09259
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Two-Dimensional C60 Nanoclusters within a Propylthiolate Matrix

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…As a result of cooperative interaction between C 60 and OT, the porous framework is formed. In an earlier study with propanethiol monolayers on Au(111), we found phase-separated C 60 and PT with no evidence of forming C 60 /PT frameworks . This suggests that the van der Waals interactions between the alkane chain and the C 60 molecule play a vital role in the C 60 /OT framework.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…As a result of cooperative interaction between C 60 and OT, the porous framework is formed. In an earlier study with propanethiol monolayers on Au(111), we found phase-separated C 60 and PT with no evidence of forming C 60 /PT frameworks . This suggests that the van der Waals interactions between the alkane chain and the C 60 molecule play a vital role in the C 60 /OT framework.…”
Section: Resultsmentioning
confidence: 56%
“…In an earlier study with propanethiol monolayers on Au(111), we found phaseseparated C 60 and PT with no evidence of forming C 60 /PT frameworks. 15 This suggests that the van der Waals interactions between the alkane chain and the C 60 molecule play a vital role in the C 60 /OT framework. The S−Au bonding alone is not sufficient to stabilize the porous framework.…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the tendency of vdW forces to guide the molecules toward a close packed arrangement at the nanoscale. [34] Hence, control over a binary molecular self-assembly system, solely reliant on vdW forces, presents significant challenges. [42,43] In an earlier study, when C 60 was deposited onto octanethiol/ Au(111), spontaneous formation of porous frameworks was observed at RT.…”
Section: Formation Of C 60 /Dt Porous Frameworkmentioning
confidence: 99%
“…[32] Earlier studies on this system unveiled phase-separated C 60 and thiols on Au(111) with no signs of a regular mixture. [33][34][35] A saturated octanethiol (OT) monolayer [33] can prevent C 60 molecules from reaching the Au(111) substrate except at locations of defects. On a propylthiol monolayer, C 60 forms close-packed domains even at 100 K with clear phase-separated domains of C 60 and thiol at RT.…”
Section: Introductionmentioning
confidence: 99%